RADISH RESPONSE TO COCOA POD HUSK AND UREA FERTILISER APPLICATIONS - Bamidele Akinrinola; Ayoade Boluwatife Ojo (Agricultura)
Radishes are vegetables cultivated and consumed for their enlarged roots. Low yield resulting from cropping intensification requires supplementation to improve or maintain yield. The perverse effects of sole inorganic fertiliser on soil health and produce quality have necessitated integrating inorganic fertiliser with farm waste as alternatives. However, there is limited information on cocoa pod husk (CPH) powder and urea fertiliser in radish production. Therefore, this study investigated the impact of CPH and urea on radish performance. A 3×4 factorial experiment was conducted using 5 kg soil to evaluate CPH at 0, 30, and 60, and urea at 0, 15, 30, and 45 kg N/ha in a randomised complete block design with six replicates. Growth and root yield data were subjected to ANOVA and significant means were separated (p < 0.05). Applying CPH reduced plant height, number of leaves, dry shoot biomass, root yield, and harvest index in radish. Increasing CPH application led to a further reduction in these parameters. Urea fertiliser application enhanced the observed parameters with the highest values at 45 kg N/ha. Sole urea application at 45 kg N/ha had a significantly higher root yield than other treatments at first cropping. However, the root yield (93.50 g/plant) was similar to CPH at 30 kg N/ha × urea at 30 kg N/ha (67.50 g/plant) and CPH at 30 kg N/ha × urea at 45 kg N/ha (75.75 g/plant) during the second cropping. Therefore, CPH at 30 kg N/ha × urea at 30 kg N/ha was suggested for radish production.